CLINICAL IMPORTANCE OF ENDOTHELIAL DYSFUNCTION AND INSULIN RESISTANCE SYNDROME IN PATIENTS WITH GOUT ASSOCIATED WITH ARTERIAL HYPERTENSION - N. N. Kushnarenko; A. V. Govorin (Столичная издательская компания, 2015)
Aim. To study the endothelium status and determine the correlation between endothelial dysfunction and glucose metabolism in men with gout associated with arterial hypertension (HT). Material and methods. Patients (n=175, all are males) with gout were enrolled into the study. Ambulatory blood pressure monitoring (ABPM) was performed in all patients. Endothelial function was studied in tests with reactive hyperemia (endothelium-dependent reaction) and nitroglycerin (endothelium independent reaction) in brachial artery by ultrasonic Doppler examination. The level of nitrite-nitrate and endothelin-1 in blood serum was determined by ELISA technique. Fasting blood glucose and oral glucose tolerance tests were performed as well as fasting insulin blood level was determined by immunoenzyme method. Insulin-resistance index (HOMA-IR) was calculated. Patients with HOMA- IR>2.77 were considered as insulin-resistant. Results. Patients with gout demonstrated endothelial deterioration associated with activation of nitroxid producing function, elevation in endothelin-1 serum level (1.36 fmol/ml [0.91; 2.32 fmol/ml] vs 0.19 fmol/ml [0.16; 0.27 fmol/ml] in controls, p<0.05) and impairments of endothelium-dependent vasodilation (6.4% [3.3; 7.3%] vs 17.8% [12.7; 23.9%] in controls, p<0.05). The revealed changes were the most marked in patients with gout associated with HT. The correlation between some endothelial dysfunction in- dices and glucose metabolism was observed. Conclusion. ABPM, brachial artery endothelium-dependent vasodilation and glucose metabolism status should be studied in patients with gout. Complex treatment of cardiovascular diseases in patients with gout should include ω-3 polyunsaturated fatty acids, angiotensin receptor antagonists should be used for antihypertensive therapy.